1995
DOI: 10.1002/ccd.1810340407
|View full text |Cite
|
Sign up to set email alerts
|

Transluminal extraction catheter for the treatment of diseased saphenous vein grafts: A multicenter experience

Abstract: To evaluate the efficacy, safety, and long-term results of atherectomy using the Transluminal Extraction catheter (TEC), patients with diseased saphenous vein grafts were enrolled in a prospective nonrandomized trial. Patients were followed to hospital discharge for acute complications and underwent routine 6-mo reevaluation with repeat cardiac catheterization to assess restenosis. Atherectomy was performed on 650 graft lesions in 538 consecutive patients (male 81%; mean age 66 yr; range 37-81). Mean graft age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…Transluminal extraction catheter treatment of diseased saphenous vein grafts has a major complication rate of 4.3% and a death rate of 3.2%, as reported in a multicenter study [11]. Distal embolization was reported in 4.3% of patients.…”
Section: Discussionmentioning
confidence: 89%
“…Transluminal extraction catheter treatment of diseased saphenous vein grafts has a major complication rate of 4.3% and a death rate of 3.2%, as reported in a multicenter study [11]. Distal embolization was reported in 4.3% of patients.…”
Section: Discussionmentioning
confidence: 89%
“…This device can be applied to symptomatic patients with ischemic coronary syndromes whose diseased saphenous vein grafts are amenable to percutaneous revascularization. The reported primary success rate is adequate and is associated with a relatively low complication rate [9,10,11]. Safian et al [12] reported procedural success in 84% of 158 saphenous vein graft lesions in 146 consecutive patients.…”
Section: Discussionmentioning
confidence: 97%
“…TEC atherectomy, which cuts and aspirates thrombus and atheromatous material, has been advocated as a unique revascularization strategy in saphenous vein grafts containing thrombotic lesions [9]. This device can be applied to symptomatic patients with ischemic coronary syndromes whose diseased saphenous vein grafts are amenable to percutaneous revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Use of stents in SVGs versus balloon angioplasty alone has been shown to improve late clinical outcome [7]. TEC atherectomy was used in occluded vein graft because it was supposed to remove intraluminal thrombus and plaque tissue and it reduced the risk of distal embolization [4,8,9]. …”
Section: Discussionmentioning
confidence: 99%